CHALLENGES IN DISTANCE LEARNING DURING THE PANDEMIC SITUATION OF CORONAVIRUS (COVID-19): A PERSPECTIVE FROM BANGLADESH - Islam, Md. Shahidul; Chowdhury, Md. Shahnur Azad; Akter, Sultana; Arafat, A. B. M. Yasir; Azam, Md. Kazi Golam (American International Journal of Social Science Research, 2021)
The purpose of the study is to identify the socio-psychological challenges that influence the distance learning education performance to be recognized and evaluated in the COVID-19 pandemic situation to develop the planning and utilization strategy for smooth and high-quality online uninterrupted teaching and learning environment in the future. A systematic random sampling survey method is used to collect information from 100 respondents on a ten-point Likert scale (1 = Least significant and 10 = Most significant to the factor of online learning). The survey response data were collected from online class experienced teachers and students (masters and graduate) from business school and science and engineering school of Int'l Islamic University Chittagong, Bangladesh (longitude 91.720902539062 and Latitude 22.495181427788) in the March-April 2021. Descriptive analysis, factor analysis, and structural equation model are used from the collected survey data by using IBM SPSS Statistics 20 and IBM SPSS AMOS 22 software to identify factors that have a significant influence on performance. The study result shows that personal factor, task assignment factor, and course factor have significant positive contribution and technical factor has a significant negative contribution to the performance in the online education. But perceive factor and social factor have no significant contribution to the performance in online education.JEL Classification Codes: I21, C38, C12.